Integrated Care Communities: Putting Change Theory into Practice. Issue 4 (19th August 2014) - Bradbury, Elizabeth
Abstract : Purpose: This paper reflects on the experience of AQuA's regional Integrated Care Discovery Community created to translate integrated care theory into practice at scale and to test ways to address the system enablers of integrated care. Design/methodology/approach: Principles of flexibility, agility, credibility and scale influenced Community design. The theoretical framework drew on relevant complexity, learning community and change management theories. Co-designed with stakeholders, the discovery-based Community model incorporated emergent learning from change in complex adaptive environments and focused bespoke support on leadership capability building. Findings: Nineteen health and social care economies participated. Kotter's eight step change model proved flexible in conjunction with large scale change theories. The tension between programme management, learning communities and the emergent nature of change in complex adaptive systems can be harnessed to inject pace and urgency. Mental models and simple rules were helpful in managing participant's desire for a directive approach in the context of a discovery programme. Research limitations/implications: This is a viewpoint from a regional improvement organisation in North West England. Originality/value: Learning from AQuA's approach may assist others in structuring large scale integrated care or complex change initiatives.